Trait self-control, emotions, and openness to alternative viewpoints - TSAI, Ming-hong (Institutional Knowledge at Singapore Management University, 2023)
We examined openness to alternative viewpoints as an unexplored consequence of trait self-control. We conducted three studies to investigate the relationship between trait self-control and openness to alternative viewpoints during situations with different opinions and to explore various emotions as potential mediators of this relationship. Our results demonstrated a positive relationship between trait self-control and openness, and this relationship was mediated by decreased anger and increased emotions with positive valence, including attentiveness and serenity. In addition, trait self-control was negatively related to fatigue, but the relationship between fatigue and openness was not consistently significant across the studies. These findings clarify the relationships between trait self-control and emotions and elucidate why individuals consider others’ different perspectives.